Pengaruh Orientasi Birokrasi Terhadap Pemerataan Layanan Kesehatan Di Kota Bandar Lampung (Studi Tentang Layanan Kesehatan Oleh Puskesmas Kedaton) - Marbaki M. S. (PUBLICA, 2012)
The problems of this research are how far the influence of bureaucracy orientation to the health service equality held by Kedaton Health Center (Puskesmas). Data are collected by means library study and field research and study the documents as well as theoretical analysis to the research object related to the main problem. Collected data are analysed by qualitative and quantitative methods as well. Quantitative methods used Rank Spearman. From this methods founded that rs is 0.703, meanwhile t-counting is 9.166 and t-table is 3.102 with significance level on 5% where freedom degree is n-2=86.. it is meant that t-counting is higher than t-table (9.166 and 3.102 respectively). So, the conclusion is Bureaucracy Orientation has high influence to the Health Service Equality at Puskesmas Kedaton. On the other hand, the result of the research accepted the research hyphothesis.